Eco-friendly synthesis and morphology-dependent superior electrocatalytic properties of CuS nanostructures. (20th August 2017) - Venkadesh, A.; Radhakrishnan, S.; Mathiyarasu, J.
Abstract: Copper sulfide with desired structure is of special interest for electrocatalytical application due to their unique physicochemical properties, simple synthesis and less toxic in nature. In this study, simple and eco-friendly (without using any template or surfactant) route for the fabrication of copper sulfide nanostructure morphologies were tuned from cauliflower, microflower to nanoparticles inter-connected network-like structures by changing the polarity of solvent medium during solvothermal synthesis. However, to the best of our knowledge, no such kinds of special three types of CuS nanostructure with excellent electro-catalytic properties using only H2 O and C2 H5 OH as the solvents have been reported in the literature. The as-prepared different CuS nanostructure was characterized using FE-SEM, HR-TEM, XRD, XPS and cyclic voltammetry. This morphological alteration able to produce several precise nanostructures with improved electrocatalytic properties that led to an excellent performance towards enzymeless glucose oxidation. The CuS inter-connected nanoparticles modified electrode displayed a synergistic effect towards the oxidation of glucose (ipa : 103 ± 5 μA) when compared to that of cauliflower (ipa : 68 ± 3.7 μA) and microflower (ipa : 60 ± 2.4 μA) modified electrode surfaces. Further, the CuS inter-connected nanoparticles modified electrode showed a wide linear range (2.0 × 10 −5 −2.5 × 10 −3  M), high sensitivity (1085 μA mM −1  cm −2 ), low detection limit (2 μM), rapid response time (< 3s), good stability, selectivity and reproducibility. The obtained sensing parameters based on CuS inter-connected nanoparticles modified electrode were superior with many reports and also comparable with few reports in the available literatures.